1999
DOI: 10.1097/00000542-199912000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Luminal Microdialysis 

Abstract: Luminal lactate concentration, as measured by microdialysis, increases substantially during gut ischemia but does not respond to systemic hyperlactatemia per se. In contrast, gut wall microdialysis cannot distinguish between gut ischemia and systemic hyperlactatemia. Gut luminal microdialysis provides a method for the assessment of intestinal ischemia with a potential for clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…More recent experiments have not shown increased vascular permeability in intestinal tissue under these conditions (Makley AT and Pritts TA, unpublished observations, 2011). Other studies have shown that sepsis- and coronary bypass surgery- induced changes in intraluminal rectal levels of lactic acid, a very small molecule compared with cytokine peptides, were not the result of lactate washout from the serum, except in cases of profound serum lactate elevation [36, 37]. In our present study, IL-6 serum levels were markedly elevated for a considerable period of time (at 1 and 3 h), and intraluminal IL-6 elevated at 6 h after shock could be a result of serum washout.…”
Section: Discussionmentioning
confidence: 99%
“…More recent experiments have not shown increased vascular permeability in intestinal tissue under these conditions (Makley AT and Pritts TA, unpublished observations, 2011). Other studies have shown that sepsis- and coronary bypass surgery- induced changes in intraluminal rectal levels of lactic acid, a very small molecule compared with cytokine peptides, were not the result of lactate washout from the serum, except in cases of profound serum lactate elevation [36, 37]. In our present study, IL-6 serum levels were markedly elevated for a considerable period of time (at 1 and 3 h), and intraluminal IL-6 elevated at 6 h after shock could be a result of serum washout.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies were able to show that a systemic lactate increase is actually a late consequence of acute mesenteric ischemia unless hypovolemia develops [10,34,35]. In similar studies, compromised mesenteric blood flow could not be detected by means of serum (arterial) lactate levels but rather by changes in the intramucosal carbon dioxide partial pressure [36], gastric intramucosal pH [37] and amount of intestinal luminal lactate [38,39,40]. Hence, numerous experimental studies also provided evidence that serum lactate is only sometimes elevated in very advanced acute mesenteric ischemia and is in general not helpful for diagnosing its early phase.…”
Section: Experimental Studies On Serum Lactate Levels In Acute Mesentmentioning
confidence: 99%
“…Experimental trials suggest that the measurement of mucosal or intestinal luminal lactate by microdialysis is a valid method to investigate and depict intestinal ischemia [16,17]. Meanwhile, luminal equilibrium dialysis [11,12] is a feasible and non-invasive method for measurements rectal lactate in clinical research.…”
Section: Discussionmentioning
confidence: 99%